Bioaccumulation of PCBs from microplastics in Norway lobster (Nephrops norvegicus): An experimental study. (November 2017) - Devriese, Lisa I.; De Witte, Bavo; Vethaak, A. Dick; Hostens, Kris; Leslie, Heather A.
Abstract: Plastic debris acts as a sorbent phase for hydrophobic organic compounds like polychlorinated biphenyls (PCBs). Chemical partitioning models predict that the ingestion of microplastics with adsorbed chemicals in the field will tend not to result in significant net desorption of the chemical to the organism's tissues. This is expected due to the often limited differences in fugacity of the chemical between the indigestible plastic materials and the tissues, which are typically already exposed in the same environment to the same chemicals as the plastic. However laboratory trials validating these model predictions are scarce. In this study, PCB-loaded microplastics were offered to field-collected Norway lobsters ( Nephrops norvegicus) during in vivo feeding laboratory experiments. Each ingestion experiment was repeated with and without loading a mixture of ten PCB congeners onto plastic microspheres (MS) made of polyethylene (PE) and polystyrene (PS) with diameters of either 500–600 μm or 6 μm. We observed that the presence of chemicals adsorbed to ingested microplastics did not lead to significant bioaccumulation of the chemicals in the exposed organisms. There was a limited uptake of PCBs in Nephrop s tail tissue after ingestion of PCB-loaded PE MS, while almost no PCBs were detected in animals exposed to PS MS. In general, our results demonstrated that after 3 weeks of exposure the ingestion of plastic MS themselves did not affect the nutritional state of wild Nephrop s. Highlights: Limited PCB bioaccumulation observed after ingestion of PCB-spiked polyethylene. Negligible PCB bioaccumulation observed after ingestion of PCB-spiked polystyrene. No effect of 3-week microplastic ingestion on nutritional state of Nephrops . No PCB depuration from Nephrops tissue to microplastics.